Industrial training report: Bank Islam Malaysia Berhad - Yuzimi, Nur Sufia Sabrina (Faculty of Business and Management, 2025)
My transforming and enlightening internship at Bank Islam Malaysia Berhad gave me the great chance to work in the department of General Administration, Property, and Project Management. Over six months, I was able by placing myself in a professional setting, bridging the gap between theoretical knowledge and real-world practices. As a pioneer in Islamic banking, Bank Islam is committed to delivering Shariah-compliant financial solutions while encouraging sustainability through Environmental, Social, and Governance (ESG) initiatives. This dual emphasis on ethical finance and sustainable development positions the bank as a leader for fostering positive change throughout the banking sector. Being part of the General Administration, Property and Project department, I was responsible for playing an integral role in managing documentation, verifying records, and monitoring assets. These responsibilities not only sharpened my technical and administrative abilities but also gave me invaluable insights into how this department contributes to achieving the bank's strategic goals. I also helped to assure the success of asset tagging tasks, which required using particular tools and adhering to strict processes for sustaining data integrity. These experiences deepened my awareness of the department's vital role in achieving the bank's strategic goals, such as increasing operational efficiency and maintaining regulatory compliance. Aside from technical capabilities, the internship helped me improve my soft skills, which included good communication, problem-solving, adaptability, and flexibility. My supervisor's constructive input and positive interactions with my team gave excellent possibilities for personal and professional development. Overall, my time at Bank Islam was both rewarding and educational, providing a solid foundation in administration and property management in the financial industry. Furthermore, the internship increased my knowledge of the critical role that Islamic banking plays in enabling sustainable development and long-term economic prosperity. This experience has equipped me well for future career issues.